Pengaruh Konten Marketing (Instagram), Citra Merek dan Review Produk Terhadap Keputusan Pembelian Scarlett Whitening - Yulianti Wardaningtri; Reyhan Gunaningrat (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to determine the significant influence of marketing content, especially Instagram social media, brand image and product reviews on purchasing decisions for Scarlett Whitening. This research uses quantitative research methods conducted online by distributing questionnaires to 92 respondents who use Scarlett Ehitening products in the city of Surakarta. The results of this research show that marketing marketing has a positive influence on purchasing decisions for Scarlett Whiteing, brand image influences purchasing decisions, but the product review variable has no direct influence on purchasing decisions for Scarlett Whitening products.